Factors Associated with Unsuccessful Treatment of Bedaquiline and or Delamanid Based Regimens in Multidrug-Resistant Tuberculosis: A Review - Nugraha Putra, Oki; Faizah, Ana Khusnul; Wijayanti D.N, Nani (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Background: Multidrug-resistant tuberculosis (MDR-TB) is a serious health concern that is difficult to treat, requiring long and complex treatment with highly effective drugs. An all-oral regimen, bedaquiline and or delamanid have already shown low unsuccessful treatment in patients with MDR-TB. Method: We comprehensively reviewed factors associated with unsuccessful treatment (death, treatment failure, and loss to follow-up) related to all oral regimen containing bedaquiline and or delamanid in patients with MDR-TB. We conducted a scoping review under the PRISMA guideline for scoping review. Results: We included seven observational studies that met the inclusion criteria. Four studies reported the concomitant use of bedaquiline and delamanid. Unsuccessful treatment ranged from 7.8% to 36.6% in regimens containing bedaquiline, delamanid, or both at six months or after treatment completion. Low rates of treatment failure and loss to follow-up were reported in the included studies. Elderly, being underweight (BMI < 18.5 kg/m2), and hepatitis C coinfection among MDR-TB patients were associated with unsuccessful treatment in most studies. None studies reported pre-XDR and XDR-TB as risk factors for unsuccessful treatment. Conclusion: In MDR-TB patients receiving regimens containing bedaquiline and delamanid, age, BMI, and hepatitis C coinfection were associated with unsuccessful treatment.